1991
DOI: 10.1111/j.1745-4549.1991.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

SENSORY, CHEMICAL and BACTERIOLOGICAL STABILITY of FRANKFURTERS CONTAINING MILK PROTEINS and CORN GERM PROTEIN FLOUR

Abstract: Self stability offiankjbters edended with milk proteins and corn germ p r e tein $ow (CGPF) stored at X-2C@r 45 days was &died by water activity, sensory evaluation, bacteriological teas, and chemical determinations of total volatile nitrogen (m, ammonia nitrogen, and TBA values. Ihe incorporation of milk proteins and CGPF affected shelf stability offimrkjbters as determined by sensory characteristics, bacteriological test, and chemical analysis. AJer 45 days of storage, the fiankjbters with CGPF added had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Therefore, competition for malonaldehyde in a system containing protein could result in reduced color development and incomplete quantification of malonaldehyde. Hung and Zayas (1992) also showed that TBA values decreased from 0.79-to 0.59-mg malonaldehyde/kg in frankfurters during 45 d of storage.…”
Section: Thiobarbutiric Acid Valuesmentioning
confidence: 78%
“…Therefore, competition for malonaldehyde in a system containing protein could result in reduced color development and incomplete quantification of malonaldehyde. Hung and Zayas (1992) also showed that TBA values decreased from 0.79-to 0.59-mg malonaldehyde/kg in frankfurters during 45 d of storage.…”
Section: Thiobarbutiric Acid Valuesmentioning
confidence: 78%
“…Hung and Zayas (1991) also informed that coliforms were heat sensitive and easily destroyed by the temperature reached during treatment in frankfurter manufacture. No sulfite-reducing Clostridium were noted in any sausages during the storage period either, indicating safe sanitary conditions in the product.…”
Section: Microbial Analysismentioning
confidence: 99%
“…Haq, Webb, Whitfield, and Ivey (1973) failed to obtain stable sausage type emulsion, which did not contain water-binding additives, at the 15% lipid level. Hung and Zayas (1991) evaluated sensory, chemical, and bacteriological stability of frankfurters containing milk protein and corn germ protein flour during 45 days of storage at 1-2°C. The addition of chitosan to 22% fat Chinese-style sausage resulted in no detrimental effect on textural properties during refrigerated storage at 4°C; all bacterial counts were lower than 7 log CFU/g after 9 weeks of storage (Lin & Chao, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of dried and processed whey as a foodstuff or adjunct for other foods including the addition to processed meats has been studied. Hung and Zayas (1991) reported that frankfurters extended with milk proteins exhibited acceptable stability. The suitability of whey is affected by the cost of drying or other processing methods.…”
Section: Introductionmentioning
confidence: 99%